Atmospheric pressure plasma assisted immobilization of hyaluronic acid on tissue engineering PLA-based scaffolds and its effect on primary human macrophages - Kudryavtseva, Valeriya; Gudima, Alexandru; Riabov, Vladimir; Liu, Tengfei; Klüter, Harald; Kzhyshkowska, Julia (Materials and design, 2017)
Bioactive polylactic acid based (PLA) scaffolds with hyaluronic acid immobilized on their surface by atmospheric pressure plasma assisted modification method were developed. By using X-ray photoelectron spectroscopy and wettability measurements it was shown that atmospheric pressure plasma treatment leads to the changes in surface chemical composition of the PLA-based scaffolds that resulted in an increased long-term hydrophilicity of the scaffolds surface. Scanning electron microscopy and mechanical studies revealed that the use of plasma for surface activation allows for the non-destructive immobilization of bioactive compounds like hyaluronic acid. The modified PLA-based scaffolds effect on the release of cytokines and matrix metalloproteinases by primary human monocyte-derived macrophages was investigated. The macrophages reaction to the scaffolds was donor-specific, however, the two best materials from immunological point of view were identified - plasma treated PLA-based scaffold and PLA-based scaffold with the least amount of immobilized hyaluronic acid. Both hyaluronic acid attachment and atmospheric pressure plasma treatment enhance PLA-based scaffolds biocompatibility. It was found that supernatants collected after the macrophages coculture with modified PLA-based scaffolds stimulate HUVECs' tube formation. The modified PLA-based scaffolds possess pro-angiogenic activity. Thus, our research offers a high-performing method for the creation of polymer-based tissue engineering scaffolds with modified bioactive surface.